Effects of cholinergic modulation on serum insulin-like growth factor-I and its binding proteins in normal and diabetic subjects - Ismail, I.S.; Miell, J.P.; Scanlon, M.F.; Peters, J.R. (Wiley, 1995)
We wished to study alterations in serum insulin-like growth factor-I (IGF-I) and its binding proteins in subjects with insulin dependent diabetes mellitus (IDDM) and possible relations with metabolic and GH secretory status, before and after cholinergic modulation. In addition, we have investigated whether cholinergic modulation exerts any effects on IGF-I secretion, independently of any actions on GH secretory status. All subjects received GH releasing hormone (GHRH) 1-44; 80 pg i.v.) alone and 60 minutes following 120 mg of pyridostigmine orally or 200 mg of pirenzepine orally. The three tests were carried out in random order at least one week apart. Blood was sampled at 15-minute intervals over 120 minutes. Twelve male subjects with IDDM and no clinical evidence of complications were selected on the basis of HbA1, levels to provide a wide range of metabolic control. Six normal male subjects were also studied. Serum IGF-I, IGF-binding protein 1 (IGFBP-1) and IGFBP-3 were measured at regular intervals throughout the study. Fasting plasma glucose and HbA1, were measured before each study to provide measures of metabolic control. Serum IGF-I and IGFBP-3 levels were significantly lower while serum IGFBP-I levels were significantly higher in the diabetic subjects. Pirenzepine had no effect on serum IGF-I, IGFBP-1 or IGFBP-3 in diabetic subjects but caused a significant increase in serum IGF-I and IGFBP-3 levels in normal subjects. Pyridostigmine had no effect on IGF-I, IGFBP-1 or IGFBP-3 in either diabetic or normal subjects. IGFBP-1 levels were significantly correlated with fasting plasma glucose but no correlation was demonstrated between measures of diabetic control and serum IGF-I or IGFBP-3 levels in diabetic subjects, nor was there any correlation between GH responses to GHRH alone or after pirenzepine or pyridostigmine pretreatment and serum levels of IGF-I, IGFBP-1 or IGFBP-3. These data confirm that subjects with IDDM have reduced serum IGF-I and IGFBP-3 and increased IGFBP-1 levels, the latter being directly related to the fasting plasma glucose concentrations. The absence of any relation between changes in the IGF-I system and altered GH neuroregulation after cholinergic modulation suggests that changes in IGF-I are not the sole contributors to the altered GH neuroregulation which occurs in IDDM. We have also shown an acute stirnulatory effect of pirenzepine on serum IGF-I and IGFBP-3 in normal subjects which is not present in IDDM although the underlying mechanism is unknown.